Beurteilungen der Schwierigkeit von Mathematikaufgaben durch Schüler und Schülerinnen (mathematica didactica, 2020)
The appropriate assessment of tasks is a central skill for the success of self-directed learning processes by learners. In order to find out how learners decide about the difficulty of a task and which reasons are relevant for their assessments, written assessments and explanations of 1169 pupils in grades 5–7 were analyzed. “Blütenaufgaben” with their non-hierarchically marked subtasks are a suitable task format for an investigation of such assessments. The students chose the easiest and most difficult subtask and explained their choices. The results show a great variety of different assessments. However, the explanations refer primarily to the learners’ own activities (easiest subtasks) and a lack of reading and task comprehension (most difficult subtask). Specific characteristics of subtasks were only mentioned seldomly.